2022
DOI: 10.3390/su14137986
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Runoff in Watersheds Located within Data-Scarce Regions

Abstract: The interest in the use of mathematical models for the simulation of hydrological processes has largely increased especially in the prediction of runoff. It is the subject of extreme research among engineers and hydrologists. This study attempts to develop a simple conceptual model that reflects the features of the arid environment where the availability of hydrological data is scarce. The model simulates an hourly streamflow hydrograph and the peak flow rate for any given storm. Hourly rainfall, potential eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The Ankara River Basin study conducted by [53], which has a 4932 km 2 drainage area, a forecasting sediment yield and streamflow using the SWAT model between 1989 and 1996 showed that the NSE value equals to 0.79 on A monthly basis for their simulated years. Similar research was conducted in the 5649 km 2 Lower Porsuk River Basin to estimate streamflow on a monthly basis using the SWAT model [51]. They found the calibration values of the NSE were 0.74 and 0.87 for the validation period, respectively.…”
Section: The Weap Model Performance: Validation and Classification Cr...mentioning
confidence: 63%
See 3 more Smart Citations
“…The Ankara River Basin study conducted by [53], which has a 4932 km 2 drainage area, a forecasting sediment yield and streamflow using the SWAT model between 1989 and 1996 showed that the NSE value equals to 0.79 on A monthly basis for their simulated years. Similar research was conducted in the 5649 km 2 Lower Porsuk River Basin to estimate streamflow on a monthly basis using the SWAT model [51]. They found the calibration values of the NSE were 0.74 and 0.87 for the validation period, respectively.…”
Section: The Weap Model Performance: Validation and Classification Cr...mentioning
confidence: 63%
“…A common statistic called Nash-Sutcliffe efficiency (NSE) is used to assess how much the residual difference deviates from the variance of the observed data. (Equation ( 1)) [2], [3].…”
Section: Nash-sutcliffe Efficiency (Nse)mentioning
confidence: 99%
See 2 more Smart Citations
“…Most continuous-time rainfall-runoff models come under the conceptual model category [8]. More focus has been placed on the use of conceptual models generally, which primarily benefits from black-box modeling and a calibration process to obtain hydrological parameters and streamflow [9,10] and to simulate groundwater levels [11,12]. The rainfall-runoff process at the catchment scale can be reliably predicted using distributed and conceptual models.…”
Section: Introductionmentioning
confidence: 99%